Designing and explaining the Quantum Productivity Model in the Ministry of Sport and Youth of the Islamic Republic of Iran - Sanavi, BA.; Razavi, MH.; Talebpour, M.; Nezhad, AK. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
This study aimed to design a quantum productivity model in the Iranian Ministry of Sport and Youth. The sample was composed of managers and staff of the Ministry of Sport and Youth of the Islamic Republic of Iran. In the first part of the study, 14 people were interviewed through thematic analysis method. In the second part, 188 people completed the questionnaire. The research instruments were an interview and a questionnaire of quantum productivity elaborated ad hoc. Data analysis was performed with WarpPLS software. After analyzing the content network, coding and screening, 8 main components of quantum productivity were finally extracted. The prediction power of the designed model was analyzed using the coefficient of determination (R2) for the dependent variables, and it was concluded that the structural model of the present study has sufficient predictive power. Considering these results, it is recommended the use of this quantum productivity model in sports organizations.